Direct mechanical thrombectomy vs. intravenous alteplase plus mechanical thrombectomy in acute ischemic stroke with anterior circulation tandem occlusions - Yang, Zhonghui; Zhang, Guang; Wu, Qiaowei; Zhu, Yujing; Xu, Shancai; Shi, Huaizhang (Frontiers in Surgery, 2025)
Background and purposeTandem occlusion is a significant risk factor for poor outcomes following intravenous thrombolysis. The necessity of bridging therapy [intravenous thrombolysis prior to mechanical thrombectomy (MT)] for patients with tandem occlusion remains controversial. This study assessed the safety and efficacy of direct MT vs. bridging therapy in patients with tandem occlusions in the anterior circulation.MethodsThis retrospective study enrolled patients with anterior circulation tandem occlusions treated with either direct mechanical thrombectomy (MT-alone group) or intravenous alteplase thrombolysis followed by MT (bridging group) between January 2019 and March 2022. The primary outcome was prespecified as a favorable outcome [modified Rankin Scale (mRS) score of 0–2] at 90 days. Secondary outcomes included successful reperfusion, overall mortality at 90 days, and rates of symptomatic intracranial hemorrhage (SICH) and asymptomatic intracranial hemorrhage (aSICH).ResultsA total of 110 patients were enrolled, with 49 in the MT-alone group and 61 in the bridging group. A favorable outcome (mRS score of 0–2) at 90 days was achieved in 25 patients (51.0%) in the MT-alone group and in 34 patients (55.7%) in the bridging group, showing no significant difference between the groups, with an adjusted odds ratio (aOR) of 1.17 (95% CI, 0.47–2.90; P = 0.743). The incidence of aSICH was higher in the bridging group than in the MT-alone group [31.1% vs. 14.3%; aOR, 2.86 (95% CI, 1.04–7.88); P = 0.042]. Rates of successful reperfusion, overall mortality at 90 days, and SICH were similar between the groups. Multivariate analysis showed that a lower baseline National Institutes of Health Stroke Scale (NIHSS) score (P = 0.005), intraprocedural tirofiban administration (P = 0.012), and internal carotid artery stent implantation (P = 0.040) were associated with a favorable outcome at 90 days.ConclusionThis study found no evidence that prior intravenous thrombolysis affects clinical or imaging outcomes in patients with acute ischemic stroke due to anterior circulation tandem occlusions after endovascular thrombectomy. Bridging therapy may be associated with an increased rate of aSICH. Intraprocedural tirofiban administration, stent implantation, and a lower baseline NIHSS score were associated with favorable outcomes.